Maternal and fetal outcomes in rheumatic heart disease in pregnancy - Sethuraman, Dhivya; Ramachandran, Nirmala; Noorjahan, SAP; Kanna, Vijay (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatic Heart Disease remains the most common type of heart disease in pregnancy in developing countries. Over a period of 2 years,129 pregnant patients with Rheumatic Heart Disease attending our outpatient department, were observed from admission till discharge and the clinical course during pregnancy and the maternal, foetal outcomes, and desire of future contraception studied. Methods: Patients were routinely examined every antenatal visit for signs of anemia and congestive cardiac failure. They were usually admitted at 28-32 weeks of gestation unless they presented with symptoms of cardiac failure earlier in pregnancy. Frequency of the antenatal visits depended on the functional cardiac status. Results: The incidence of heart disease was 0.96% for all deliveries during our study period. The incidence of RHD was 71.6%. 65.1% of women gave a h/o rheumatic fever. 45(34.9%) patients had undergone surgical correction and 84(65.1%) did not undergo surgical correction. 95.3% had moderate to severe disease but only 18.6% were in NYHA class III/IV. Hence severity of disease did not correlate with NHYA class. 76.7% of women had vaginal delivery. LSCS was done for obstetric reasons alone. Conclusion: The association of the pre pregnancy functional class with the risk of maternal events raises attention to the possibility of reducing these complications in pregnant women with mitral stenosis by means of early interventions aimed at improving their functional class.